75.6k views
2 votes
If f(x)=(2x^2)-1, find:
-f(3x-1)+2

User Kragan
by
4.5k points

2 Answers

3 votes
-f(3x-1) + 2 = -18x2 + 12x+1
User Cagatay Ulubay
by
5.0k points
3 votes

Answer:

-f(3x - 1) + 2 = -18x² + 12x + 1

Explanation:

Step 1: Find f(3x - 1)

f(3x - 1) = 2(3x - 1)² - 1

f(3x - 1) = 2(9x² - 6x + 1) - 1

f(3x - 1) = 18x² - 12x + 2 - 1

f(3x - 1) = 18x² - 12x + 1

Step 2: Plug in f(3x - 1)

-(18x² - 12x + 1) + 2

Step 3: Evaluate

-18x² + 12x - 1 + 2

-f(3x - 1) + 2 = -18x² + 12x + 1

User MaMazav
by
4.7k points